Long-Term Ultrasound Follow-Up After Pediatric Adnexal Torsion - Smorgick, Noam; Nir, Omer; Pekar-Zlotin, Marina; Maymon, Shlomit; Pansky, Moty; Maymon, Ron (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose Conservative surgical management of adnexal torsion in pre- and post-menarchal girls by de-torsion and adnexal conservation is the current standard of care. The aim of this study is to investigate the long-term outcome of adnexal torsion in this population in terms of ultrasound appearance and ovarian volume.Methods Patients who were surgically treated for adnexal torsion and were < 18 years old at time of surgery were prospectively invited for ultrasound follow-up. The ultrasound exam included measurements of ovarian volume and grayscale appearance including identification of ovarian follicular activity.Results 84 cases of torsion in this population were identified, and 37 of them were included in the study. Of those, the affected ovary could not be demonstrated on follow-up scan in six (16.2 %) cases. A difference of ≥ 2 cm3 in ovarian volume between the affected and non-affected ovaries was diagnosed in 12 (32.4 %) cases, but follicular activity was observed in 10 of those. Thus, possible ovarian injury (including cases of non-demonstrated ovary and volume difference of ≥ 2 cm3 between the affected and non-affected ovaries) was found in 18 (48.6 %) cases. Of the clinical and surgical parameters (including age at time of torsion, duration of pain prior to admission, cystectomy procedure and intraoperative “bluish” appearance of the ovary), only the presence of fever on admission was significantly associated with possible ovarian injury (p = 0.01).Conclusion Long-term ultrasound follow-up of pre- and post-menarchal girls with a history of adnexal torsion may identify patients with adversely affected ovarian volume. The significance of this finding in terms of fertility is unknown.
Keywords: ultrasound; adnexal torsion; ovarian volume